The Law Relating to Medical Confidentiality and Patient's Right of Privacy - Jahn Kassim, Puteri Nemie (2012)
The integrity of the doctor-patient relationship is based on safeguarding patient’s confidential information. Medical ethics stress the importance of confidentiality based on the assumption of an individual's right to privacy and on the assumption that the consequences of breaching this right to privacy normally outweigh possible benefits. However, the duty of confidentiality is by no means an absolute concept. The patient’s interest in his privacy must be balanced with other potentially conflicting interests. In providing care, medical professionals often find themselves trapped between conflicting duties and obligations.